Landscaping of Montenegrin resorts: Adriatic coast and the Bay of Kotor - Hryniewicz, Małgorzata; Dmytrenko, Andrii; Kashchenko, Oleksandr; Tretiak, Yuliia; Krupa, Michał; Yablonska, Hanna; Yaremchuk, Olena (Landscape Architecture and Art, 2022)
The article analyzes the features of landscape design of two different subzones of Montenegro – the northern part of the Adriatic coast and the Bay of Kotor. The aim of the article is to identify the main natural and urban planning factors that determine the nature of greening in the resort towns of the North Coastal region of Montenegro, characteristic techniques of greening and basic approaches to landscape design of the territory of recreational facilities. The methods of geospatial analysis, historical analysis and comparative analysis were used. As a result of the study, the determining role of relief in the predominance of certain methods of greening of resort towns was proven.Comparison of greening techniques of the resort towns of Herceg Novi and Budva showed greater compliance with the local flora of grrening in Herceg Novi and greater exotic landscaping of the tourist area of the Adriatic coast – so called Budva Riviera. Seven characteristic methods of landscape design in the resort towns of the North Coastal region of Montenegro have been identified. Two main approaches to the landscape design of the territory of recreational facilities have been identified: "closed", when a closed environment of a recreational facility is created according to the "city within a city" principle with extensive use of stylization techniques and exotic plants, and "open", when views on the attractive natural landscapes or on historical buildings, and landscaping mainly uses local plant species.